OBSTRUCTIVE JAUNDICE FOLLOWING MIBG THERAPY IN MALIGNANT PHEOCHROMOCYTOMA: A CASE REPORT - Fauzi, Nur Syafiqah Binti Mohd; Nordin, Hidayatil Alimi Bin Keya; Voon, Tong Chin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Malignant pheochromocytoma is a rare neuroendocrine tumor with potential for local invasion and distant metastasis. In inoperable cases, nonsurgical options include I-131 metaiodobenzylguanidine (MIBG) therapy. MIBG-related complications may occur, especially in patients with bulky or anatomically complex tumors. We describe a case of post-MIBG ascending cholangitis due to tumor-related biliary obstruction. CASE A 49-year-old Kadazan Muslim female with hypertension, type 2 diabetes, dyslipidaemia, and previous strokes was diagnosed in August 2022 with inoperable malignant right adrenal pheochromocytoma. She presented with right hypochondriac pain, weight loss, palpitations, diaphoresis, and postural hypotension. Imaging revealed a right suprarenal mass (6.3 × 4.9 × 7.5 cm) invading the inferior vena cava and right renal vein. Elevated urine normetanephrine and positive DOTATATE, FDG-PET, and MIBG scans confirmed a functional tumor. Due to high surgical risk, she declined surgery and underwent right adrenal artery embolization with stable disease on follow-up. In July 2024, she received high-dose I-131 MIBG therapy (211 mCi) for palliative intent. Eight days post-therapy, she developed fever and jaundice. Imaging revealed intrahepatic biliary dilatation secondary to tumor compression at the porta hepatis. She was diagnosed with ascending cholangitis complicated with gram-negative sepsis and thrombocytopenia. She was managed with intravenous antibiotics, biliary stenting and supportive care. CONCLUSION Obstructive jaundice is a rare but serious complication following MIBG therapy. In this case, tumor compression near the porta hepatis—likely exacerbated by post-therapy inflammation or necrosis—led to biliary obstruction. Although preoperative biliary stenting is standard in pancreaticobiliary malignancies, its use in neuroendocrine tumors, including pheochromocytoma, is not well defined. This case supports the potential role of pre-emptive biliary decompression in select high-risk patients undergoing MIBG therapy. Multidisciplinary planning is essential for risk stratification and outcome optimization.